My adventure an Iban warrior's autobiography - Robert Rizal Abdullah (Metier Books, 2008)
Robert Rizal Abdullah is a modern Iban warrior. He is a direct descendent of the famous Iban warriors, famed for their exemplary courage, prowess in the battlefield, and uncanny skills in tracking enemies in the jungles. He tells his life story - how he grew up in an Iban longhouse community in Sarawak just after World War II, and how he managed to escape the stranglehold of poverty, completing his education, and finally joining the Malaysian Army at a time when the communist insurgency was at its raging height, both in Malaya and Sarawak. My Adventure is an astonishing story of Robert's adventures from his boyhood through his twenty five years in the Malaysian Army. Fanned by the legendary fighting spirit of his forefathers, he fought communist terrorists. For his courageous attack on an enemy camp in 1973 in Sarawak, he was awarded the nation's second highest award for bravery, the Panglima Gagah Berani (PGB). AboutAuthor: Robert Rizal Abdullah (Robert Madang Langi ) was born on October 6, 1948. Brought up by his brother Upi, a police officer, he completed his primary education in Kapit, Lutong and Bintulu, and his secondary education at the premier Tanjong Lobang School in Miri, Sarawak. Unable to simply watch the ongoing insurgency, first in Malaya, then in the Brunei Rebellion of 1962, and concerned by the imminent threat of another communist insurgency in Sarawak and the Indonesian confrontation against Malaysia, he volunteered to join the Malaysian Army. His military service became a rewarding career that spanned twenty-five years.